Gut microbiota-estrogen axis: Its influence on female health outcomes – A narrative review - Atoum, Manar; Padma, Kanchi (Acta Biomedica Atenei Parmensis, 2025)
Background: During women’s lifetime, gut microbiota plays roles in the reproductive endocrine system influencing hormones such as estrogen, androgens, insulin and other hormones. Gut microbiota trigger estrobolome to produce β-glucuronidase that deconjugates estrogens into their active forms. An imbalance in the microbiome affects microbial diversity, decreases estrogen deconjugation and reduces the circulating estrogen that leads to many diseases like polycystic ovary syndrome (PCOS) and diabetes. This study aims to review the studies that correlate estrogen, gut microbiota and female health. Material and methods: published research articles (period from 2018 to 2024) were assessed through Science Direct, PubMed, Scopus, and Google Scholar using these terms: gut microbiota, human, female health, estrogen, and estrobolome (total articles 78). Articles were selected and tracked to avoid any duplication by excluding animal studies articles, those with insufficient data, and those without interesting outcomes. Articles were selected that determine any association between gut microbiota, estrogen, and female health (total 12) as in Figure 1. Gut microbiota plays an important role in the women’s endocrine system, and β-glucuronidase is critical for estrogen metabolism. Distribution in estrogen metabolism causes gut microbial dysbiosis diseases, such as PCOS, obesity and diabetes. In post-menopausal women, high estrogen was associated with an increase in α-diversity microbiota. Lactobacillus was an abundant bacteria in pre and post-menopausal groups. Non-ovarian estrogens were associated with abundant microbiota that produce β-glucuronidase, such as Ruminococcaceae and Clostridia. This article reviews the previous studies about gut microbiota, estrogen, diabetes, obesity and PCOS. Conclusion: This review highlights the association between estrogen, gut microbiota diversity, diabetes, obesity and PCOS. Understanding the complex association between estrogen and the gut microbiota may attract attention to prevent and treat gastrointestinal disorders by microbiota modulation.